MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - ROHMIYATI, ATIEK; TUHUTERU, LAROS (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
Preliminary observation showed that lack of interest toward civic education subject (PKn) was the cause for unenthusiastic attitude in the learning activities. College students regard PKn as a subject that focuses only on rote. The less emphasis on reasoning aspect was the cause for the lack of learning interest toward Civic Education (PKn) among college students. Therefore, it is essential to have a learning strategy that focuses on students and has the ability to create a fun atmosphere needed to improve students’ result on civic education (PKn). For the purpose, we choose Problem Based Learning as a method to improve students’ participation in learning activities which in turn will help improve college students’ result in Civic Education (PKn) subject, especially on students of hospitality study program of Politeknik Negeri Media Kreatif. Based on observation result and discussion, it showed that Problem Based Learning was able to improve students and also lecturer activities in the learning process. The learning aspects developed include growing college students’ courage in asking and throwing opinions, motivating and raising enthusiasm among college students, improving college students’ ability in group/class discussion, improving good relationship between college students and lecturer, good relationship among college students and improving college students’ participation in the learning activities. The improvement in college students’ active participation during learning activities was followed by improvement in college students’ achievement. The achievement improvement was considerably higher compared to preliminary observation. ABSTRAKBerdasarkan hasil pengamatan dan pengalaman selama ini, mahasiswa kurang aktif dalam kegiatan pembelajaran PKn. Mahasiswa nampak kurang tertarik dengan mata kuliah Pendidikan Kewarganegaraan (PKn) karena selama ini Pendidikan Kewarganegaraan (PKn) dianggap sebagai mata kuliah yang hanya mementingkan hafalan semata, kurang menekankan aspek penalaran sehingga menyebabkan rendahnya minat belajar. Pendidikan Kewarganegaraan (PKn) mahasiswa di kampus dengan strategi pembelajaran yang berpusat pada mahasiswa dan penciptaan suasana yang menyenangkan sangat diperlukan untuk meningkatkan hasil belajar mahasiswa dalam mata kuliah Pendidikan Kewarganegaraan (PKn). Dalam hal ini Penulis memilih model pembelajaran berbasis masalah (problem based learning) sebagai upaya meningkatkan partisipasi mahasiswa dalam proses pembelajaran diharapkan mampu meningkatkan prestasi belajar para mahasiswa khususnya dalam matakuliah Pendidikan Kewarganegaraan (PKn) di Politeknik Negeri Media Kreatif, di Prodi Perhotelan. Berdasarkan hasil penelitian adanya penerapan pembelajaran berbasis masalah (problem based learning) mampu meningkatkan peran/aktivitas mahasiswa maupun dosen dalam proses pembelajaran. Aspek-aspek yang dikembangkan meliputi: menumbuhkan keberanian mahasiswa dalam bertanya dan mengemukakan pendapat, motivasi dan kegairahan dalam mengikuti pembelajaran, mengembangkan kemampuan mahasiswa dalam mengikuti diskusi kelompok/kelas, hubungan baik mahasiswa dengan dosen, hubungan baik mahasiswa dengan mahasiswa lain dan mengembangkan partisipasi mahasiswa dalam pembelajaran. Dengan penerapan pembelajaran berbasis masalah (problem based learning) menunjukkan adanya peningkatan partisipasi aktif mahasiswa selama proses pembelajaran yang diikuti dengan peningkatan prestasi belajar mahasiswa. Peningkatan prestasi belajar terlihat pada hasil test pertama dibandingkan dengan hasil test kedua saat penelitian dilaksanakan.